Bacterial cellulose-hydroxyapatite nanocomposites for bone regeneration - Saska, S. [UNESP]; Barud, H. S. [UNESP]; Gaspar, A. M M [UNESP]; Marchetto, Reinaldo [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (Hindawi, 2011)
The aim of this study was to develop and to evaluate the biological properties of bacterial cellulose-hydroxyapatite (BC-HA) nanocomposite membranes for bone regeneration. Nanocomposites were prepared from bacterial cellulose membranes sequentially incubated in solutions of CaCl2 followed by Na2HPO4. BC-HA membranes were evaluated in noncritical bone defects in rat tibiae at 1, 4, and 16 weeks. Thermogravimetric analyses showed that the amount of the mineral phase was 40-50 of the total weight. Spectroscopy, electronic microscopy/energy dispersive X-ray analyses, and X-ray diffraction showed formation of HA crystals on BC nanofibres. Low crystallinity HA crystals presented Ca/P a molar ratio of 1.5 (calcium-deficient HA), similar to physiological bone. Fourier transformed infrared spectroscopy analysis showed bands assigned to phosphate and carbonate ions. In vivo tests showed no inflammatory reaction after 1 week. After 4 weeks, defects were observed to be completely filled in by new bone tissue. The BC-HA membranes were effective for bone regeneration. © 2011 S. Saska et al.